Authority in Intimations of Global Law. (3rd July 2017) - Capps, Patrick
ABSTRACT: Neil Walker, in his recent monograph entitled Intimations of Global Law, provides an explanation of how authority emerges in the pluralist global legal landscape. Authority, in perhaps a modern restatement of the traditional consent-based view, emerges from contestation and comprise in the relations between the institutions and bodies that populate this landscape (this is called voluntas ). From these relations emerge shared, and indeed universal, values such as a respect for 'basic rights' and 'autonomy' (this is called ratio ). In this essay, the dynamic between voluntas and ratio is considered, and the importance of dissent and resistance within the global landscape as a means to generate ratio is highlighted.